The unexpected case of reactions of halogens and interhalogens with halide substituted Pd(ii) σ-butadienyl complexes. Issue 28 (30th June 2016) - Scattolin, Thomas; Visentin, Fabiano; Santo, Claudio; Bertolasi, Valerio; Canovese, Luciano
Abstract : Palladium σ-butadienyl derivatives react with halogens and interhalogens, under mild experimental conditions, to induce the substitution of the halogen to coordinated palladium and to the terminal butadienyl carbon without extrusion of the butadienyl fragment. Abstract : We have experimentally studied and theoretically interpreted the addition under stoichiometric conditions of halogens or interhalogens to σ-butadienyl palladium complexes bearing the heteroditopic thioquinolines as spectator ligands. The observed reactions do not involve the expected extrusion of the butadienyl fragment but rather the unpredictable substitution of the halide coordinated to palladium and in some cases also of that bound to the terminal butadienyl carbon. We have explained this peculiar reactivity with a mechanistic hypothesis based on a sequence of selective processes of oxidative addition and reductive elimination involving Pd(iv ) intermediates.